Resident Management System for Lestari Mansions with Role-Based Access Control - Chin, Hui Yee; Mohd Foozy, Cik Feresa (Applied Information Technology And Computer Science, 2025)
This resident management system is developed for Lestari Mansions, Seri Kembangan to manage the residents efficiently. The existing resident management at Lestari Mansions does not provide an access control mechanism and paper-based information can be accessed easily by all the residents, committee members, and security guards. Therefore, this study aimed to develop a system that allows only the authorized users to login to the system and perform specific tasks by implementing Role-Based Access Control (RBAC). Agile methodology is used in the development of this system using the Java programming language. The developed resident management system is expected to improve the efficiency of the existing management process while ensuring data security. User acceptance testing conducted with two committee members and three residents verified the functionality and usability of the system.